The Ability of Lytic Staphylococcal Podovirus vB_SauP_phiAGO1.3 to Coexist in Equilibrium With Its Host Facilitates the Selection of Host Mutants of Attenuated Virulence but Does Not Preclude the Phage Antistaphylococcal Activity in a Nematode Infection Model - Głowacka-Rutkowska, Aleksandra; Gozdek, Agnieszka; Empel, Joanna; Gawor, Jan; Żuchniewicz, Karolina; Kozińska, Aleksandra; Dębski, Janusz; Gromadka, Robert; Łobocka, Małgorzata (Frontiers in Microbiology, 2019)
Phage vB_SauP_phiAGO1.3 (phiAGO1.3) is a polyvalent Staphylococcus lytic podovirus with a 17.6-kb genome (Gozdek et al., 2018). It can infect most of the Staphylococcus aureus human isolates of dominant clonal complexes. We show that a major factor contributing to the wide host range of phiAGO1.3 is a lack or sparcity of target sites for certain restriction-modification systems of type I and II in its genome. Phage phiAGO1.3 requires for adsorption β-O-GlcNAcylated cell wall teichoic acid, which is also essential for the expression of methicillin resistance. Under certain conditions an exposure of S. aureus to phiAGO1.3 can lead to the establishment of a mixed population in which the bacteria and phages remain in equilibrium over multiple generations. This is reminiscent of the so called phage carrier state enabling the co-existence of phage-resistant and phage-sensitive cells supporting a continuous growth of the bacterial and phage populations. The stable co-existence of bacteria and phage favors the emergence of phage-resistant variants of the bacterium. All phiAGO1.3-resistant cells isolated from the phage-carrier-state cultures contained a mutation inactivating the two-component regulatory system ArlRS, essential for efficient expression of numerous S. aureus virulence-associated traits. Moreover, the mutants were unaffected in their susceptibility to infection with an unrelated, polyvalent S. aureus phage of the genus Kayvirus. The ability of phiAGO1.3 to establish phage-carrier-state cultures did not preclude its antistaphylococcal activity in vivo in an S. aureus nematode infection model. Taken together our results suggest that phiAGO1.3 could be suitable for the therapeutic application in humans and animals, alone or in cocktails with Kayvirus phages. It might be especially useful in the treatment of infections with the majority of methicillin-resistant S. aureus strains.